2022
DOI: 10.1096/fj.202101734rrr
|View full text |Cite
|
Sign up to set email alerts
|

Lamina propria interleukin 17 A aggravates natural killer T‐cell activation in autoimmune hepatitis

Abstract: Autoimmune hepatitis is an interface hepatitis characterized by the progressive destruction of the liver parenchyma, the cause of which is still obscure. Interleukin (IL)‐17A is a major driver of autoimmunity, which can be produced by innate immune cells against several intracellular pathogens. Here, we investigated the involvement of IL‐17A in a mice model of immune‐mediated hepatitis with the intestine exposed to Salmonella typhimurium. Our results showed more severe Concanavalin (Con) A‐induced liver injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Natural killer (NK) cells are crucial in the initial onset of disease, and their response is followed by adaptive T-(Th1, Th17 and cytotoxic T cells) and B-cell responses, as evidenced by liver histology and serology. [48][49][50] Innate response is subsequently followed by T-cell mediated adaptive hepatitis. These tissue destructive effector T cells are controlled by regulatory T cells (Tregs).…”
Section: Cell-based Therapymentioning
confidence: 99%
“…Natural killer (NK) cells are crucial in the initial onset of disease, and their response is followed by adaptive T-(Th1, Th17 and cytotoxic T cells) and B-cell responses, as evidenced by liver histology and serology. [48][49][50] Innate response is subsequently followed by T-cell mediated adaptive hepatitis. These tissue destructive effector T cells are controlled by regulatory T cells (Tregs).…”
Section: Cell-based Therapymentioning
confidence: 99%
“…In Table 1, we summarized all the main studies where NKT cells were specifically investigated in murine ConA-induced hepatitis as the main experimental model of AIH [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Nkt Cells In Autoimmune Hepatitis: Evidence From Basic Researchmentioning
confidence: 99%
“…The recent study by Chen et al suggested an important role of IL-17A in ConA-related liver inflammation since this cytokine was able to induce a strong activation of NKT cells and stimulate their IL-4 production. Notably, the main source of this NKT cell-activating IL-17A was identified in the mucosal-associated invariant T (MAIT) cells residing in the gut and was triggered by a microbial agent [59]. IL-17 can also be expressed by NKT cells (as previously mentioned), and its role as an effector cytokine in liver injury has been described in a murine model of acute experimental hepatitis induced by the administration of αGalCer, characterized by a significant infiltration of neutrophils and proinflammatory monocytes [63].…”
Section: Nkt Cells In Autoimmune Hepatitis: Evidence From Basic Researchmentioning
confidence: 99%
“…Administration of concanavalin A (ConA) has been widely recognized as an appropriate model of immune‐mediated liver injury in mice. ConA‐induced liver injury is characterized as excessive activation of T cells, natural killer T (NKT) cells, macrophages, and cytokine release, such as tumor necrosis factor‐α (TNF‐α), interferon‐gamma (IFN‐γ), and interleukin‐6 (IL‐6), which lead to hepatocyte apoptosis 3,4 . Recent studies have reported that depletion of macrophage by clodronate liposomes or gadolinium chloride alleviated ConA‐induced liver injury but did not inhibit cytokine release 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…ConA-induced liver injury is characterized as excessive activation of T cells, natural killer T (NKT) cells, macrophages, and cytokine release, such as tumor necrosis factor-α (TNF-α), interferon-gamma (IFN-γ), and interleukin-6 (IL-6), which lead to hepatocyte apoptosis. 3,4 Recent studies have reported that depletion of macrophage by clodronate liposomes or gadolinium chloride alleviated ConA-induced liver injury but did not inhibit cytokine release. 5,6 Our previous study showed that dampening macrophage necroptosis can alleviate ConA-induced liver injury by blocking TNF receptor (TNFR)-1.…”
Section: Introductionmentioning
confidence: 99%